Of Natural Metaphors. Derrida on the Eluded Necessity of the Hegelian System (Revista Eletrônica Estudos Hegelianos, 2015)
The paper focuses on what Derrida understands as the eluded necessity of the Hegelian concept of life as well as of the living organization of the Hegelian system: why must we recur to images borrowed from natural life in order to speak of the life of the spirit? As Derrida points out in Glas, on the one hand, Hegel conceives of the natural image as a metaphor or rhetorical operation, insofar as it is based on the analogy (and difference) between nature and spirit (nature’s being the spirit outside itself). On the other, the natural metaphor is claimed as necessary to account for the life of the spirit (the negative process of the syllogism) and, thus, for the structure of history and of the system. The argument of the paper is that, in pointing to what remains unexplained in Hegel’s recourse to natural metaphors, Derrida proposes to reconsider natural life (namely, the circulation of singular and mortal germs) as that from which the life of the spirit and the living system cannot be liberated.